Magnetic and magnetoelastic properties of Zn-doped cobalt-ferrites-CoFe2-xZnxO4 (x=0, 0.1, 0.2, and 0.3) - Somaiah, Nalla; Jayaraman, Tanjore V.; Joy, Pattayil Alias; Das, Dibakar (Journal of Magnetism and Magnetic Materials, 2012)
Cobalt-ferrite (CoFe2O4) based materials are suitable candidates for magnetomechanical sensor applications owing to a strong sensitivity of their magnetostriction to an applied magnetic field. Zn-doped cobalt-ferrites, with nominal compositions CoFe2-xZnxO4 (x=0-0.3), were synthesized by auto-combustion technique using Co-, Fe-, and Zn-nitrate as precursors. X-ray spectra analysis and Transmission electron microscopy studies revealed that the as-prepared powders were comprised of nano-crystalline (similar to 25-30 nm) cubic-spinel phase with irregularly-shaped grains morphology along with minor impurity phases. Calcination (800 degrees C for 3 h) of the precursor followed by sintering (1300 degrees C for 12 h) resulted in a single phase cubic-spinel structure with average grain size similar to 2-4 mu m, as revealed from scanning electron micrographs. The magnitude of coercive field decreases from similar to 540 Oe for x=0 to 105 Oe for x=0.30. Saturation magnetization initially increases and peaks to similar to 87 emu/g for x=0.2 and then decreases. The peak value of magnetostriction monotonically decreases with increasing Zn content in the range 0.0-0.3; however the piezomagnetic coefficient (d lambda/dH) reaches a maximum value of 105 x 10(-9) Oe-1 for x=0.1. The observed variation in piezomagnetic coefficient in the Zn substituted cobalt ferrite is related to the reduced anisotropy of the system. The Zn-doped cobalt-ferrite (x=0.1) having high strain derivative could be a potential material for stress sensor application. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Cobalt-ferrite; Magnetic-properties; Magnetostriction